Talking sex: Thai Phet and its connection to Thai drag performance as reflected by the language of kathoey performers in Chiang Mai - Shuttleworth, Clayton (Humanities, Arts and Social Sciences Studies, 2023)
Drag performance has enjoyed increasing popularity around the globe, largely thanks to the success of US reality show RuPaul’s Drag Race. This specific brand of drag from the West has recently gained popularity in Thailand. Mainstream conceptualizations of drag performance often rely on a binary gender imaginary that differs from Thailand’s phet system. This qualitative study aimed to investigate contemporary discourse regarding Thai phet through interviews with Thai performers of drag and cabaret in Chiang Mai and to highlight how Thai drag negotiates the Thai phet imaginary. Eight performers based in Chiang Mai, representing a variety of performance backgrounds and phet presentations, were interviewed. Interviews were transcribed and underwent narrative and discourse analysis. The participants used phet vocabulary fluidly and contextually. The terms LGBT(Q), gay, sao song, hua pok, and kathoey were at times used to indicate distinct categories. At other times, however, any one of these words could be a part of a larger category of kathoey. The participants used the term kathoey to refer at different times to a particular feminine aesthetic presentation, an internal sense of self, or an over-the-top demeanor. Participants sometimes used language influenced by a binary understanding of mainstream drag performance but also acknowledged that Thai drag doesn’t fit that binary. The space of this newer brand of drag performance aligns well with an expansive category of kathoey. In this way, Thai drag actually challenges both Western concepts of sex/gender/sexuality and dominant conceptualizations of Thai phet, celebrating other ways of being for Thai kathoey.